Identification of two LGBPs (isoform1 and isoform2) and their function in AMP expression and PO activation in male hepatopancreas. Issue 95 (December 2019) - Zhang, Zhuoxing; Han, Keke; Dai, Xiaoling; Zhang, Ruidong; Cao, Xueying; Zhang, Chao; Wang, Kaiqiang; Huang, Xin; Ren, Qian
Abstract: Two lipopolysaccharides (LPS) and β-1, 3-glucan binding protein (LGBP), designated as PcLGBP isoform1 and PcLGBP isoform2, respectively, were identified from Procambarus clarkii in this study. The full-length cDNA of PcLGBP isoform1 was 1308 bp containing an open reading frame (ORF) of 1113 bp encoding a protein of 370 amino acids. The full-length cDNA of PcLGBP isoform2 was 1440 bp containing an ORF of 1245 bp encoding a protein of 414 amino acids. Predicted PcLGBP isoform1 and PcLGBP isoform 2 proteins contained a signal peptide, a glycoside hydrolase domain, and a low-complexity region. The difference between the two LGBP isoforms was that PcLGBP isoform2 had 44 more amino acids behind the signal peptide than the PcLGBP isoform1. The PcLGBP isoform1 and PcLGBP isoform2 transcripts mainly expressed in the hepatopancreas in female and male crayfish. Moreover, the expression levels of the two genes in the hepatopancreas were higher in male than that in female crayfish. Upon being challenged with Vibrio parahaemolyticus or LPS, the expression levels of PcLGBP isoform1 and PcLGBP isoform2 in the hepatopancreas of female and male crayfish were most significantly up-regulated at different time points. The transcripts of anti-lipopolysaccharide factors (ALF5, ALF6, ALF8, and ALF9) and crustins (CRU1, CRU2, CRU3, and CRU4) were evidently down-regulated in the hepatopancreas of V. parahaemolyticus -challenged total PcLGBP (including PcLGBP isoform1 and PcLGBP isoform2)-silenced male crayfish. In addition, the phenoloxidase (PO) activity in the hepatopancreas of male crayfish was evidently higher than that of female crayfish. PcLGBP knock down could significantly decrease the PO activity in the hepatopancreas lysate (HLS) in male crayfish. The PO activity of male crayfish HLS was significantly increased when incubated with a mixture of recombinant LGBP protein and LPS or β-1, 3 glucan. We conclude that LGBP isoforms from P. clarkii function as a pattern recognition protein for recognizing and binding LPS and β-1, 3 glucan, and thus regulate the synthesis of antimicrobial peptides and activate the prophenoloxidase system. Highlights: PcLGBP isoforms have different expression level in male and female crayfish. The expression levels of the two LGBP isoforms were regulated by V. parahaemolyticus and LPS. AMP synthesis and PO production were regulated by PcLGBP. The mixture of rPcLGBP and LPS or β-1, 3 glucan could activate the proPO system.